2008
DOI: 10.1152/ajpregu.00027.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroidectomy, T4, and DITPA replacement on brain blood vessel density in adult rats

Abstract: Schlenker EH, Hora M, Liu Y, Redetzke RA, Morkin E, Gerdes AM. Effects of thyroidectomy, T4, and DITPA replacement on brain blood vessel density in adult rats. Am J Physiol Regul Integr Comp Physiol 294: R1504-R1509, 2008. First published March 19, 2008 doi:10.1152/ajpregu.00027.2008.-In hypothyroid patients, altered microvascular structure and function may affect mood and cognitive function. We hypothesized that adult male hypothyroid rats will have significantly lower forebrain blood vessel densities (BVD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Minor modifications in structure may alter the efficiency of thyroid analog uptake (6), TH receptor binding (14), or recruitment of coactivators or corepressors (33). Our previous study and the current one indicate that DITPA can be administered at a dose which promotes a healthy vasculature in the brain and heart with limited metabolic effects (25). It would be helpful to determine the angiogenic properties of other available thyroid analogs to better understand their potential therapeutic utility.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Minor modifications in structure may alter the efficiency of thyroid analog uptake (6), TH receptor binding (14), or recruitment of coactivators or corepressors (33). Our previous study and the current one indicate that DITPA can be administered at a dose which promotes a healthy vasculature in the brain and heart with limited metabolic effects (25). It would be helpful to determine the angiogenic properties of other available thyroid analogs to better understand their potential therapeutic utility.…”
Section: Discussionmentioning
confidence: 87%
“…DITPA can also induce angiogenesis and arteriolar growth in postinfarcted myocardium (31,35) and increase the protein expression of vascular endothelial growth factor (VEGF) 164 , VEGF 188 , basic fibroblast growth factor (bFGF or FGF-2), angiopoietin-1, and Tie-2 (32). Our previous studies also demonstrated that DITPA administration increased myocardial blood flow in BIO-TO2 cardiomyopathic hamsters (13) and prevented the loss of brain blood vessels in rats as they developed hypothyroidism (25). However, phase-2 clinical trials conducted by the Department of Veterans Affairs and Titan Pharmaceuticals, in the management of patients with New York Health Association class III and IV heart failure, were terminated recently due to body mass loss, although this occurred in overweight rather than normal-weight individuals (clinicaltrials.gov).…”
mentioning
confidence: 85%
“…Schlenker et al (2008) reported that hypothyroidism in rats induces a decrease in brain blood vessel density. Replacement with 3,5-diiothyroprionic acid and T 4 effectively prevented the effects of hypothyroidism on cardiac function and increased blood vessel density.…”
Section: Discussionmentioning
confidence: 99%
“…Kuzman and colleagues (28,29) have shown that agonist thyroid hormone (thyromimetic) analogs are proangiogenic in the postinfarcted hamster heart by a pathway that involves Akt signaling. Thyroid hormone also has substantial proangiogenic activity on brain blood vessels (57). Angiogenic activity of iodothyronine analogs that is initiated at the integrin receptor has been demonstrated in the blood vessels of the chick chorioallantoic membrane (CAM) model (11,45,47) and the human dermal microvascular endothelial cell (HDMEC) sprouting model (46).…”
Section: Translational Implications Of Nongenomic Actions Of Thyroid mentioning
confidence: 99%